KEY PATHOGENETIC ASPECTS AND CLINICAL RELEVANCE OF MECHANICAL DYSSYNCHRONY - Yu. V. Stavtseva; S. V. Villevalde; A. V. Sveshnikov; J. D. Kobalava (Столичная издательская компания, 2015)
Review of scientific evidences on contemporary concepts of the pathogenesis of mechanical dyssynchrony and its significance in patients with chronic heart failure is presented.